Art and the greater good : ecology and the leisure economy : a thesis presented in partial fulfillment of the requirements for the degree of Masters in Fine Arts at Massey University, Wellington, New Zealand - Wallis, Samantha (Massey University, 2010)
Art and the Greater Good: Ecology and the Leisure Economy is a research project concerned with exploring how one could alternatively address the environmental issues of our day through site-specific art. Central to this investigation has been attending to the ways historical and contemporary accounts of environment politics, site specificity, land and environmental art could resonate within a more modest artistic gesture. The resulting work Would you go on without me? reflects the possibility of this by its position in an indeterminate zone; that draws together the demotic, gardening, rainwater harvesting, play and ecology into the manifold of environmental art.
Keywords: Site-specific art; Water harvesting; Plants in art; Environmental art; Fields of Research::410000 The Arts